Effect of essential sandalwood aromatheraphy oil (santalum album l.) on intensity decresing pain in the first stage of labor at Elliani Clinic - Umamy, Farida; Sitorus, Ririn Anggriani; Wati, Dewi Widya (Institute of Computer Science (IOCS), 2024)
The traditional sandalwood plant is a producer of essential oils because of the distinctive nature of the heartwood and contains oil with a specific aroma. Sandalwood oil has several functions, including as an aromatheraphy ingridient which is very beneficial for human health. Sandalwoodoil can be used to cure stomach aches, skin ailments, kidney infections various inflammations, sedatives, pain relievers. this was to determine the effect of giving sandalwood aromatheraphy to the intensity of decreasing labor pain in the first stage of labor. This type of research used the Quasy Eksperimen method with pretest-posttest case control design in this study, the samples taken were mothers in the first stage of labor. 30 people. The sampling technique uses total sampling. Statistical test results using the uji t- paired sampel test. Analysis of the data obtained, namely the intensity of labor pain in the first stage before administration of sandalwood essential oil aromateraphy, the majority experienced severe pain intensity as many as 16 respondents (53,3%) and 14 respondents (46,7%) in the moderate category. While the intensity of labor pain in the first stage after admiinistration of sandalwood essential oil aromatherapy, the majority experienced mild pain intensity as many as 18 respondents (60,0%), 10 respondents (33,3%) in the moderate category and respondents (6,7%) in the moderate category heavy. The results of the analysis showed that giving sandalwood essential oil aromatherapy proved effective in reducing the intensity of labor pain in the first stage of labor.